Optimizing Organic Digital Marketing Strategy for Social Media Instagram Arirang with the Engagement Rate and Followers Growth Method: Optimalisasi Strategi Pemasaran Digital Organik terhadap Sosial Media Instagram Arirang dengan Metode Engagement Rate dan Followers Growth - Bova Ayesha Ameer Wibowo; Mega Cattleya Prameswari Annissa Islami (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This study aimed to optimize the organic digital marketing strategy of Instagram for the Arirang brand by utilizing Engagement Rate (ER) and Followers Growth as evaluation metrics. The activity involved collecting interaction data from Instagram Insights over a three-month period, calculating ER and Followers Growth, and analyzing the impact of these metrics on content performance and audience engagement. The results demonstrated a high ER of 189.61%, indicating exceptional audience interaction and content performance, along with a significant followers growth of 80.52%, showcasing the effectiveness of interactive content strategies such as giveaways and collaborations with Key Opinion Leaders (KOLs). These findings highlight the potential for sustainable audience engagement and brand awareness growth when leveraging social media analytics in digital marketing strategies. Future recommendations include regular monitoring of account insights, experimentation with content formats, and expanded collaborations to reach a broader audience segment.